EFFECT OF AL-QURAN MUROTTAL THERAPY ON SLEEP QUALITY OF NON-HEMORRHAGIC STROKE PATIENTS (PENGARUH TERAPI MUROTTAL AL-QURAN TERHADAP KUALITAS TIDUR PENDERITA STROKE NON HEMORAGIK) - Ashaeryanto, Ashaeryanto; Nurdin, Anwas; Akbar, Muhammad; Basri, Muhammad Iqbal; Muis, Abdul (Psikoislamedia: Jurnal Psikologi, 2022)
This study was aimed to identify the effect of Al-Quran Murottal therapy on sleep quality of non-hemorrhagic stroke patients. This was a quasi design experiment with a control group, involving 18 respondents as the result of simple randomization. Samples were divided into two groups: intervention and control, who met the inclusion and exclusion criteria. Sleep quality was measured by the Pittsburg Sleep Quality Index (PSQI). This study showed that there was a significant difference in sleep quality before and after Al-Quran Murottal therapy (p-value 0,018) even though the result was not significant in the control group (p-value 1,000). There was a significant effect of Al-Quran Murottal therapy for the sleep quality of non-hemorrhagic stroke patients.